MERDEKA BELAJAR KAMPUS MERDEKA: MEMAKNAI MAHASISWA AGAMIS PRODUKTIF DI ERA SOCIETY 5.0 - Uswatun Hasanah; Farell Alhafiz; Hikma Apriyani; Nor Rochmatul Wachidah (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2023)
Merdeka Belajar Kampus Merdeka (MBKM) is present in order to answer the demands of the needs of the Society 5.0 era, which requires quality improvement in various aspects of the implementation of education, especially Islamic University. Islamic University must adapt to existing progress while still holding on to Islamic teachings. Therefore, the research aims to examine the essence of the MBKM policy in interpreting productive religious students in the era of Society 5.0. This research is qualitative library research; the research data were collected using documentation techniques and analyzed using content analysis. The results of the study show that MBKM defines productive religious students as those who are able to combine spirituality, academics, and social responsibility in their learning experiences with the aim of developing themselves holistically and preparing themselves to play an active role in society. In conclusion, the MBKM program supports quality human resources who adhere to religious values, have good academic achievements, and make positive contributions to society.